2018
DOI: 10.1371/journal.pone.0191399
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of background parenchymal enhancement in the contralateral breast with patient and tumor characteristics of MRI-screen detected breast cancers

Abstract: PurposeHigher background parenchymal enhancement (BPE) could be used for stratification of MRI screening programs since it might be related to a higher breast cancer risk. Therefore, the purpose of this study is to correlate BPE to patient and tumor characteristics in women with unilateral MRI-screen detected breast cancer who participated in an intermediate and high risk screening program. As BPE in the affected breast may be difficult to discern from enhancing cancer, we assumed that BPE in the contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Another limitation of the study is that our vessel detection method used T 1 ‐weighted, fat‐suppressed, and contrast‐enhanced subtraction MR images as inputs. Therefore, it is currently limited in patients with marked background parenchymal enhancement . Additionally, the individual AIFs were extracted from the thoracic arteries, which are small compared to the 3 × 3 windows used to generate the average signal intensity time course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the study is that our vessel detection method used T 1 ‐weighted, fat‐suppressed, and contrast‐enhanced subtraction MR images as inputs. Therefore, it is currently limited in patients with marked background parenchymal enhancement . Additionally, the individual AIFs were extracted from the thoracic arteries, which are small compared to the 3 × 3 windows used to generate the average signal intensity time course.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is currently limited in patients with marked background parenchymal enhancement. 44 Additionally, the individual AIFs were extracted from the thoracic arteries, which are small compared to the 3 × 3 windows used to generate the average signal intensity time course. This measurement could be affected by partial volume and motion artifacts, which could lead to an AIF with an underestimated enhancement rate and/or peak height.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with invasive breast cancer, one study demonstrated an association between increased BPE and hormone (estrogen and progesterone) receptor positivity, the presence of lymphovascular invasion, and close surgical margins . Another study demonstrated that increased BPE was associated with lower tumor grade, as well progesterone receptor (PR) positivity . While these studies need to be further verified in larger, prospective studies, their findings point to the potential for BPE on preoperative breast MRI to provide prognostic information to help determine the need for neoadjuvant and/or adjuvant therapy and tailor optimal surgical approaches.…”
Section: Bpe As a Predictor Of Treatment Outcomesmentioning
confidence: 99%
“…Previous studies have shown that the relative amounts of FGT on mammography are associated with the risk of breast cancer 2–4 . Also, recent studies have proved that increased BPE is associated with increased risk of breast cancer 5–10 and overall treatment outcomes 11–15 …”
mentioning
confidence: 99%